Development of Song-Q_Education Teaching Aids Based on Music Using Artificial Intelligence (AI) in Teaching Mechanical Design in Design and Technology Form 2/ Pembangunan Bahan Bantu Mengajar Song-Q_Education Berasaskan Muzik Menggunakan Kecerdasan Buatan (AI) Dalam Pengajaran Reka Bentuk Mekanikal Di Reka Bentuk Dan Teknologi (RBT) Tingkatan 2 (Sains Humanika, 2025)
The use of teaching aids has now become a necessity in every teaching and learning (PdP) session. This is due to the national education policies introduced by the ministry, which aim to produce holistic individuals in all aspects. In addition, the rapid development of technology has impacted all sectors, including education. The capabilities of artificial intelligence (AI) technology in processing data, generating responses, and creating specific content in a short time can no longer be denied. Therefore, this study aims to focus on the development of teaching aids based on musical intelligence (as referred to in the multiple intelligences theory) with the assistance of AI technology. The teaching aids developed in this study is called Song-Q_Education, which integrates musical elements and AI technology (such as ChatGPT, WeSing), opening new opportunities for the development of music-based teaching aids. This study employs the ADDIE model as its main framework. A qualitative approach is used to collect data from informants and experts. A total of 6 teachers were involved in this study, with 3 informants (analysis phase) and 3 experts (evaluation phase) participating to address the objectives/research questions. The informants focused on identifying the essential elements needed for music-based teaching aids, while the experts focused on evaluating the usability of the Song-Q_Education teaching aids. The data collected were analyzed using thematic analysis, resulting in the identification of themes and sub-themes. In summary, five key elements were identified from the interviews conducted. Additionally, the experts’ responses regarding the usability of the Song-Q_Education teaching aids were positive. Finally, the researcher discusses recommendations for future studies, specifically for the development of auditory-based (listening) teaching aids.
Keywords: Teaching aids, musical intelligence, artificial intelligence (AI), mechanical design, interactive learnin